Pengaruh Dana Tabarru, dan Dana Syirkah Terhadap Total Asset (Studi Kasus Pada PT. Asuransi jiwa syariah jasa mitra abadi tbk 2018-2021) - Wika Asnantiawati; Dian Hakip Nurdiansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Islamic insurance continues to grow in Indonesia, one of the accounts available at Islamic insurance companies is syirkah funds and tabarru funds, in Islamic insurance using the tabarru contract, where these funds are provided by insurance members as a form of grant funds, which cannot be withdrawn by the giver funds, tabarru funds will be used to help fellow members if needed with certain conditions, in addition to syirkah funds, namely funds received in the form of investments with a period of time from individuals and other parties, this journal is to see whether there is an effect of tabarru funds and also syirkah funds to total assets, the authors conducted this study using quantitative methods withSPSS media, where the authors took secondary data sources, this was to see how much influence tabarru funds and temporary syirkah funds had on the total assets of PT. asuransi jiwa syariah tbk 2018-2021 analysis is presented in the form of multiple regression, which had previously been tested for classical assumptions, namely the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation, after which the f test and t test were carried out, after being tested the authors got the results in this study that the funds tabarru and temporary syirkah funds have no effect on total assets, and the results of the f test show that both tabarru funds and syirkah funds do not have a very strong impact on total assets, it can be seen that if tabarru funds or syirkah funds experience changes, it does not result in changes in the total asset value side at PT. Asuransi jiwa syariah jasa mitra abadi tbk.